The roles of teacher and students via blended problem-based learning: Improving students’ mastery of three representation levels of chemistry - Ibrahim, Mokhzani; Jamaludin, Khairul Azhar (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
The current practice in teaching Chemistry subject is found to be teacher-centered where teachers engage actively in transmitting knowledge while students act as passive recipients of knowledge. This might affect students’ mastery in learning three representation levels of Chemistry (macroscopic, microscopic and symbolic). As a result, students tend to form a non-scientific understanding and develop an alternative concept. The shift to Blended Problem-based Learning (BPBL) is therefore potential to help overcome this problem. Thus, this study is aimed at investigating the roles of teacher and students in overcoming the formation of alternative concepts for three representation levels of Chemistry in BPBL. This study applies a case study research design. Two teachers and 20 students from two different Fully Residential Schools are selected using purposive sampling technique. Data are collected through observations and students’ documents, and analysed thematically. Overall, the findings of this study shows that teacher acts as mediator in giving immediate feedbacks and corrections on students’ alternative concept while students act as evaluator in analyzing and evaluating other group’s answers. As a conclusion, the implementation of BPBL is found beneficial to overcome the formation of alternative concept and thus helps to improve students’ mastery of three representation levels of Chemistry.